Conversatorio con importantes actores de la Red Latinoamericana de Educación en Enfermería (ReLEdEn), Red Iberoamericana de Seguridad del Paciente y GROWING UP FOUNDATION. - Llivi Ruilova, Danny Vicente (2023)
Lic. Esthela Guerrero, coordinator of the Nursing Degree Training and Linkage Network (REVIFGE) and professor at the Faculty of Health Sciences, participated in the conversation through the zoom platform, with important actors from the Latin American Network of Nursing Education (ReLEdEn), Ibero-American Patient Safety Network and GROWING UP FOUNDATION, with the aim of signing important alliances and agreements to strengthen international mobility, Teaching, Research and Linkage.